Classification of f-Biharmonic Curves in Lorentz–Minkowski Space - Li Du; Juan Zhang (Journal of Mathematics)
In this paper, we firstly derived the equations for the curves of a Lorentz–Minkowski space L3 to be f-biharmonic. Then, using these equations, we classify such unit speed curves in L3.